Transforming Medication Order Processing Through Workflow Automation: A Scholarly Analysis of Large-Scale Pharmacy System Modernization - Chandra Kiran Yelagam (International Journal of Computational and Experimental Science and Engineering, 2026)
Current pharmacy practice is burdened with increasing prescription volumes, disparate clinical information, and emerging regulatory requirements that cannot be adequately addressed by current monolithic, batch-oriented medication order processing systems. This scholarly analysis examines how transforming medication order processing systems into intelligent, event-driven pharmacy workflows addresses critical challenges, including poor productivity in labor-intensive verification processes, disparate clinical data across information silos, and cognitive overload stemming from inefficient system architectures. Through the synthesis of published research, industry best practices, and architectural patterns documented in healthcare informatics literature, this work demonstrates how modern automated workflow architectures utilizing microservices decomposition, event-driven orchestration engines, and decoupled clinical decision logic enable real-time routing, parallel processing, self-adaptive workflows, and increased throughput velocity under stringent safety constraints. Evidence from diverse pharmacy implementation contexts reveals that workflow automation reduces manual review requirements by 40-50%, decreases verification turnaround times by 30-35%, and improves medication safety through consistent drug interaction screening and contraindication evaluation protocols. This framework uniquely integrates strangler pattern migration architecture with parallel clinical validation and real-time safety monitoring controls specifically tailored to pharmacy workflow constraints and regulatory requirements. The analysis establishes that successful modernization approaches incorporate incremental implementations following the strangler pattern, comprehensive user adoption strategies with purposeful change management, and multi-disciplinary governance frameworks focused on clinical appropriateness and regulatory compliance throughout the automation lifecycle. This work contributes to the healthcare informatics literature by providing an integrated architectural framework synthesizing event-driven computing paradigms, microservices design patterns, and clinical governance principles specifically tailored to pharmacy workflow modernization contexts.